(untitled) (Scientific journal of the Fergana State University, 2023)
The article discusses the differences between sentences of the verb and nominal types, about the logical-grammatical, grammatical and stylistic-pragmatic types of subjects; furthermore, the issues of sentences, the use of which is impossible without a subject, is considered in the article.